A Multimedia System for the Management of Intangible Cultural Heritage. Issue 2 (June 2015) - Artese, Maria Teresa; Gagliardi, Isabella
UNESCO, in its 2003 Convention for the Safeguarding of the Intangible Cultural Heritage, obliges State Parties to inventory cultural heritage and making those inventories accessible. This process is a rather complex activity, involving different skills and competences, such as ethnographers, social history experts, etc. who detect cultural heritage to be inserted in the catalog, identifying the best practices and defining what kind of information to keep track of. In this paper we will present three environments that compose a framework for the inventorying, cataloging, searching and browsing of multimedia digital objects related to ICH (Intangible Cultural Heritage), developed to design and implement the AESS archive (Archive of Ethnography and Social History of Lombardy Region): the data concern mainly popular traditions handed down generation by generation, such as traditional fairs, popular songs, and customs.